Design and construction of the complex steel structure for the Amager Bakke waste‐to‐energy plant. Issue 1 (January 2017) - Hauptenbuchner, Johannes
Abstract: Amager Bakke (English: Amager slope) is the name of Copenhagen's new waste‐to‐energy‐plant located on the Amager peninsula. Once finished, it will be one of the largest incinerators in northern Europe and will be used for the combined production of district heat and electricity. On top of the waste‐to‐energy plant there will be a landscaped park featuring artificial ski slopes and a viewing platform. The support structure is mainly formed by a steelwork. The model‐based design and construction of the complex, three‐dimensional steel structure proved to be a challenging task for all the engineers and companies involved.